Bem-Estar no Manejo Pré-Abate e a Influência na Qualidade da Carne Suína. - Aguiar, Andressa Silveira (Universidade Federal do Tocantins, 2023)
Pigs destined for slaughtering are subject to a number of new conditions, known as pre-slaughter management when taken together. These conditions impose on these animals fasting, mixing of unknown animals, embarking, transporting, landing, and human interaction, which practices affect the well-being of the animal. A decisive step, control in the stages before slaughtering requires a careful look at animal welfare practices, since the lack of preparation, knowledge or even their estrangement affect numerous losses caused by depreciation of carcasses and deviations of meat quality. In addition to the economic losses brought about by the inability of these practices to feed, consumers have become more demanding in order to prioritize animal welfare at all stages of the pork production chain, especially those of quality and food safety. Therefore, well-being goes the opposite way, that is, coming from the outside to the inside, for it expresses itself first in society; which increasingly requires such practices to be applied.